Terrestrial myriametric radio burst observed by IMAGE and Geotail satellites. Issue 3 (15th March 2013) - Fung, Shing F.; Hashimoto, Kozo; Kojima, Hirotsugu; Boardsen, Scott A.; Garcia, Leonard N.; Matsumoto, Hiroshi; Green, James L.; Reinisch, Bodo W.
Abstract: [1] We report the simultaneous detection of a terrestrial myriametric radio burst (TMRB) by IMAGE and Geotail on 19 August 2001. The TMRB was confined in time (0830–1006 UT) and frequency (12–50 kHz). Comparisons with all known nonthermal myriametric radiation components reveal that the TMRB might be a distinct radiation with a source that is unrelated to the previously known radiation. Considerations of beaming from spin‐modulation analysis and observing satellite and source locations suggest that the TMRB may have a fan beamlike radiation pattern emitted by a discrete, dayside source located along the poleward edge of magnetospheric cusp field lines. TMRB responsiveness to IMF Bz and By orientations suggests that a possible source of the TMRB could be due to dayside magnetic reconnection instigated by northward interplanetary field condition. Key Points: We identify first observation of a terrestrial myriametric radio burst (TMRB). TMRB radiation characteristics and possible source location are described. TMRB may be associated with high‐latitude dayside reconnection process.